Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Our platform provides a seamless experience for finding precise answers from a network of experienced professionals. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
i solved this one by substitution. When you are solving for two equations you can do this.
y=x-5
y=-2x+1
substitute the y in one of the equations to find x
x-5=-2x+1
x=-2x+6
3x=6
x=2
then you plug in that number to one of the equations
y=2-5
y=-3
y=x-5
y=-2x+1
substitute the y in one of the equations to find x
x-5=-2x+1
x=-2x+6
3x=6
x=2
then you plug in that number to one of the equations
y=2-5
y=-3
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.